Analisis Perilaku Percaya Diri pada Usia 5-6 Tahun : Faktor Lingkungan, Pola Asuh, Interaksi Sosial, Motivasi, dan Perkembangan Kognitif Anak - Sri Ramla Wati Monoarfa; Rabiatul Adawiya Lapasu; Tri Hastri Bumulo; Prahara M.Marjuni; Fiola Indah Putri Pratama (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This research explores self-confidence in early childhood, focusing on children aged 5–6 years at TK Pembina Ki Hajar Dewantara. Self-confidence is recognized as an essential part of affective development, influencing personality formation, social-emotional competence, and readiness to face life’s challenges. The study applied a descriptive quantitative design with five children from group B as participants. Data collection was carried out through observation using structured assessment instruments to identify indicators of self-confidence, such as performing in front of others, leading simple tasks, expressing opinions, and engaging in role-play activities. Findings showed that all subjects obtained an average score of 4, categorized as Very Well Developed (BSB). These results indicate that the children displayed strong belief in themselves, decision-making ability, and emotional stability when interacting with others. The study further highlights the significant contribution of teachers and parents in nurturing children’s confidence by providing guidance, encouragement, recognition, and creative learning strategies, including role-play and artistic activities. Consequently, building self-confidence from an early stage is a critical foundation for ensuring children’s success academically and socially.